ANALISIS HADIS JUAL BELI DAN RIBA DALAM KITAB MIR’ATU AL-THULLAB FI TASHIL MA’RIFAT AL AHKAM KARYA ABDURRAUF AL-SINKILI - Martiani, Shofia; Navisyah, Syahrotun; Muhid (LPPM IAIN Kediri, 2023)
Kitab Abdurrauf al-Sinkili